2015
DOI: 10.4103/0974-7753.153450
|View full text |Cite
|
Sign up to set email alerts
|

Hair cosmetics: An overview

Abstract: Hair cosmetics are an important tool that helps to increase patient's adhesion to alopecia and scalp treatments. This article reviews the formulations and the mode of action of hair cosmetics: Shampoos, conditioners, hair straightening products, hair dyes and henna; regarding their prescription and safetiness. The dermatologist's knowledge of hair care products, their use, and their possible side effects can extend to an understanding of cosmetic resources and help dermatologists to better treat hair and scalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
165
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(173 citation statements)
references
References 55 publications
(153 reference statements)
1
165
0
7
Order By: Relevance
“…People with curly and wavy hairs are more likely to have oily scalp but less oil on the hair fiber surface. Sebaceous glands of African descendants are frequently less active when compared with the Caucasian ones [79]. A study [57] revealed that, in the composition of African hair fiber, the lipid content in terms of cholesterol-ester, free-fatty-acids and cholesterol-sulfate is higher than in the other two ethnic hair types.…”
Section: Differences On Ethnic Hair Fiber Characteristics and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…People with curly and wavy hairs are more likely to have oily scalp but less oil on the hair fiber surface. Sebaceous glands of African descendants are frequently less active when compared with the Caucasian ones [79]. A study [57] revealed that, in the composition of African hair fiber, the lipid content in terms of cholesterol-ester, free-fatty-acids and cholesterol-sulfate is higher than in the other two ethnic hair types.…”
Section: Differences On Ethnic Hair Fiber Characteristics and Propertiesmentioning
confidence: 99%
“…The surfactants can be classified into four groups according to the electric charge of the polar extremity: anionic, cationic, amphoteric and nonionic [79,80]. Modern shampoos contain a mixture of surfactants to provide different cleaning levels according to hair type [80].…”
Section: Shampoomentioning
confidence: 99%
“…For most of the BHFs, the maximum fiber length attainable is 60 mm which in turn would limit the choices of fiber orientation in developing BHFRPCs. In terms of chemical modification of BHFs, the hydrophobic epithelial cuticle may be disrupted and expose the hydrophilic cortex of the BHFs and this is likely to result in a swollen fiber [48]. Swollen fibers impede mechanical properties improvement in NFRPCs [49].…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The inside layer (Medulla) is present only in thick hair. Its function has not been clearly defined [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers make use of different hair care products to change the physical appearance of hair, such as shampoos, conditioners, styling products, hair dye and hair straighteners [2].…”
Section: Introductionmentioning
confidence: 99%